2007
DOI: 10.1038/sj.npp.1301631
|View full text |Cite
|
Sign up to set email alerts
|

Proton Magnetic Resonance Spectroscopy During Initial Treatment With Antipsychotic Medication in Schizophrenia

Abstract: Reduced brain N-acetyl-aspartate (NAA) has been repeatedly found in chronic schizophrenia and suggests neuronal loss or dysfunction. However, the potential confounding effect of antipsychotic drugs on NAA has not been resolved. We studied 32 minimally treated schizophrenia patients and 21 healthy subjects with single-voxel proton magnetic resonance spectroscopy ( 1 H-MRS) of the frontal and occipital lobes, caudate nucleus, and cerebellum. Concentrations of NAA, Choline, and Cre were determined and corrected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
3
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 48 publications
(59 reference statements)
4
73
3
1
Order By: Relevance
“…We observed an effect of treatment irrespective of antipsychotic for NAA, Glx and Creatine, but this appears to be caused by higher doses pretreatment with other antipsychotics, as results disappeared after correction for baseline haloperidol equivalents. Other studies have also failed to show an effect of treatment on prefrontal NAA levels with both strong and weak D2 antagonists in recently medicated patients [37][38][39]. It has been reported that NAA did initially not decrease after treatment [34], but eventually did after multiple years [33], although the authors could not confirm whether these effects were specific to antipsychotic exposure.…”
Section: Researchcontrasting
confidence: 46%
“…We observed an effect of treatment irrespective of antipsychotic for NAA, Glx and Creatine, but this appears to be caused by higher doses pretreatment with other antipsychotics, as results disappeared after correction for baseline haloperidol equivalents. Other studies have also failed to show an effect of treatment on prefrontal NAA levels with both strong and weak D2 antagonists in recently medicated patients [37][38][39]. It has been reported that NAA did initially not decrease after treatment [34], but eventually did after multiple years [33], although the authors could not confirm whether these effects were specific to antipsychotic exposure.…”
Section: Researchcontrasting
confidence: 46%
“…Although some markers (e.g., NAA) (Bustillo et al 2008) have been measured repeatedly, to date no studies have assessed the trajectory of neurobiological markers specifically associated with a psychotic episode and subsequent remission. The challenge for future research is to characterise the nature of brain trajectories (e.g., linear v. non-linear; acute v. gradual) occurring across the stages and phases of schizophrenia psychoses as well as in the context of neurodevelopment.…”
Section: A Guide For Future Imaging Workmentioning
confidence: 99%
“…There were no differences in gray matter, white matter, and cerebrospinal fluid (CSF) proportions at each time point between cytidine and placebo groups. Metabolite concentrations were arithmetically corrected for voxel CSF proportion assuming a metabolite concentration of zero in CSF (Bustillo et al, 2008;McLean et al, 2001).…”
Section: Mri/mrs Acquisition and Processingmentioning
confidence: 99%